Studies on Leaf Blight Disease of Sissoo (Dalbergia sissoo Roxb.) in Bangladesh - Chowdhury, S.; Rashid, H.; Ahmed, R.; Haque, M. M. U. (International Journal of Economic Plants, 2020)
The outbreak of leaf blight disease in sissoo (Dalbergia sissoo Roxb.) was detected in different plantation areas of Sylhet, Bangladesh, during surveys conducted in November 2019. Isolates were consistently recovered from the necrotic region of the blight infected leaves. Isolates grown on potato-dextrose-agar (PDA) showed greyish-white cottony mycelia with a concentric zone of orange conidial masses. Average conidia length and width ranging from 13.5-17.7 µm and 3.5-5.3 µm, respectively. In the pathogenicity test, the pathogen was able to cause infection on detached healthy leaves and spots developed were similar to those observed on the leaves affected in nature. However, the pathogen produced disease symptoms in wounded leaves but did not produce any symptoms on the non-wound ones. Findings also suggested that the pathogen was equally virulent to three-leaf grades (young, middle and mature-aged). Based on the above morphological features, the pathogen was identified as Colletotrichum sp. Molecular identification is needed to determine the pathogen up to species. The observation of the pathogen causing leaf blight disease of sissoo in Bangladesh has severe implications regarding the management of plantations and nurseries. More surveys are needed to determine the distribution and extent of damage caused by the pathogen in other regions.